Does Antitrust Need to be Modernized? - Dennis W. Carlton (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
In 2002, Congress established the Antitrust Modernization Commission to address whether the antitrust laws needed to be changed in light of globalization and rapid technological change. This paper addresses that question. Although the basic framework of the antitrust laws is suitable to deal with current economic conditions, the paper identifies several areas where antitrust can be improved. The paper first examines whether the proper criterion for antitrust should be total or consumer surplus. Then it identifies some key issues that need to be clarified and explains how they should be clarified. Those issues include market definition, merger policy and the treatment of efficiencies, the interaction of antitrust and intellectual property, exclusionary conduct, the right of indirect purchasers to sue, and the proper allocation of responsibility between regulation and antitrust.
Keywords: 330